Parathyroid Hormone-Related Peptide Elicits Peripheral TRPV1-dependent Mechanical Hypersensitivity - Shepherd, Andrew J.; Mickle, Aaron D.; Kadunganattil, Suraj; Hu, Hongzhen; Mohapatra, Durga P. (Frontiers in Cellular Neuroscience, 2018)
Bone metastasis in breast, prostate and lung cancers often leads to chronic pain, which is poorly managed by existing analgesics. The neurobiological mechanisms that underlie chronic pain associated with bone-metastasized cancers are not well understood, but sensitization of peripheral nociceptors by tumor microenvironment factors has been demonstrated to be important. Parathyroid hormone-related peptide (PTHrP) is highly expressed in bone-metastasized breast and prostate cancers, and is critical to growth and proliferation of these tumors in the bone tumor microenvironment. Previous studies have suggested that PTHrP could sensitize nociceptive sensory neurons, resulting in peripheral pain hypersensitivity. In this study, we found that PTHrP induces both heat and mechanical hypersensitivity, that are dependent on the pain-transducing transient receptor potential channel family vanilloid, member-1 (TRPV1), but not the mechano-transducing TRPV4 and TRPA1 ion channels. Functional ratiometric Ca2+ imaging and voltage-clamp electrophysiological analysis of cultured mouse DRG neurons show significant potentiation of TRPV1, but not TRPA1 or TRPV4 channel activation by PTHrP. Interestingly, PTHrP exposure led to the slow and sustained activation of TRPV1, in the absence of any exogenous channel agonist, and is dependent on the expression of the type-1 parathyroid hormone receptor (PTH1), as well as on downstream phosphorylation of the channel by protein kinase C (PKC). Accordingly, local administration of specific small-molecule antagonists of TRPV1 to mouse hindpaws after the development of PTHrP-induced mechanical hypersensitivity led to its significant attenuation. Collectively, our findings suggest that PTHrP/PTH1-mediated flow activation of TRPV1 channel contributes at least in part to the development and maintenance of peripheral mechanical pain hypersensitivity, and could therefore constitute a mechanism for nociceptor sensitization in the context of metastatic bone cancer pain.